(untitled) (Italian Journal of Public Health, 2004)
HCV infection is today the viral epidemic disease second only to AIDS. It is estimated that 3% of the world population is infected by hepatitis C and chronic related diseases, with markedly different prevalences between different geographical areas and different categories in the same area. The Authors analyse the epidemiological data available to trace the situation worldwide, in Europe, in Italy and in Campania, currently and in the last few years. Also researched was the role that the risk factors related to the different transmission routes play in the spread of the infection. Despite the decrease in the incidence reported in recent years, the numerous cases linked to drug abuse, to infections occurring while in health care and after unsafe sexual intercourse reveal the need for further information to be spread on HCV infection and on its modes of transmission.